Development of Wordwall-Assisted Educational Game Media on Fractions to Improve Mathematical Literacy in Elementary School Students - Ridwan Syaidi Ridwan; Tustiyana Windyani; Dadang Jaenudin (PRISMA, 2026)
This study aims to develop Wordwall-assisted educational game media on fraction material to improve the mathematical literacy of elementary school students. The low scores of Indonesian students in international assessments such as PISA 2022, combined with the abstract nature of fraction concepts and the dominance of teacher-centered conventional instruction, highlight the urgent need for innovative, technology-integrated learning media. This research employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects included material, media, and language expert validators, 15 teachers for feasibility testing, and 38 fifth-grade students at SDN Batukarut, Sukaraja, Sukabumi, as the experimental group. Data were collected through expert validation sheets, teacher and student response questionnaires, and mathematical literacy tests. Results indicate that the developed Wordwall-based educational game achieved a "very valid" rating from expert validators. Teacher and student responses were both categorized as "very good." The effectiveness test using a one-group pretest-posttest design showed a significant improvement in students' mathematical literacy, with an N-gain value in the medium-high category. This study recommends the integration of Wordwall-assisted educational games as a standard digital learning medium in elementary mathematics classrooms, particularly for abstract topics such as fractions.